Numerical Simulation and Experimental Study on Flow Pressure Drop of Ice Slurry in Piping Systems - Liu Shengchun; Song Ming; Dai Baomin; Sun Zhili; Hao Ling; Hao Ying (Zhileng xuebao)
Based on particle phase dynamics, the Euler-Euler model in FLUENT was selected to numerically simulate the ice slurry flowing in a piping system such as a straight pipe, 90° elbow pipe, and T type pipe without considering the ice melting process. The simulation results revealed that the pressure drops in these three pipe types at the entrance were obvious. In the 90° elbow pipe, the inside pressure was less than the outside pressure after the bend, and the highest and lowest pressures appeared in the shunt of the T type pipe. The ice slurry flow experiment results showed that the specific pressure drop increased with the velocity and ice particle fraction. Among the three pipe types, the pressure drop of the straight pipe was the smallest, and that in the T type pipe was the largest. A comparison of the numerical simulation and experimental results showed that the pressure drop was consistent with the flow velocity within an error range of 20%, but the simulated value was larger than the experimental value at high flow rates. Determining the flow characteristics of an ice slurry will play an important role in the popularization of ice slurry engineering applications.